THE RELIABILITY ANALYSIS OF WELDING ROBOTS BASED ON T-S FUZZY FAULT TREE - LIANG Fen; WANG Zhen (Jixie qiangdu)
According to the less effectiveness and difficulty in fault diagnosis of welding robots for its lots of uncertain faults phenomena and faults causes,this paper proposes the Fuzzy Fault Tree Analysis apply to welding robots fault diagnosis. Based on the analysis of welding machine structure and the T-S fuzzy fault tree analysis method,taking the torch’s gesture and suspension height setting of welding machine as an example,the fuzzy fault tree based on T-S model is established,and the reliability analysis for welding robots is discussed. The result shows that this method can find the weak link of the system without understanding the failure mechanism accurately,and can overcome the shortcomings of traditional fault tree analysis.